Enhanced recognition of disgusted expressions occurs in spite of attentional avoidance at encoding - Zalmenson, Tom; Azriel, Omer; Bar-Haim, Yair (Frontiers in Psychology, 2023)
Introduction Negative emotional content is prioritized in memory. Prioritized attention to negative stimuli has been suggested to mediate this valence-memory association. However, research suggests only a limited role for attention in this observed memory advantage. We tested the role of attention in memory for disgusted facial expressions, a powerful social–emotional stimulus. Methods We measured attention using an incidental, free-viewing encoding task and memory using a surprise memory test for the viewed expressions. Results and Discussion Replicating prior studies, we found increased attentional dwell-time for neutral over disgusted expressions at encoding. However, contrary to the attention-memory link hypothesis, disgusted faces were better remembered than neutral faces. Although dwell-time was found to partially mediate the association between valence and memory, this effect was much weaker than the opposite direct effect. These findings point to independence of memory for disgusted faces from attention during encoding.